Grinding of Si3N4 ceramic using nano-particles suspended in vegetable oil based lubricants / Yusuf Suleiman Dambatta - Yusuf Suleiman , Dambatta (2018)
Silicon nitride (Si3N4) ceramic is highly desired in various engineering applications due to its exceptional properties. However, machining the Si3N4 ceramic suffers huge setbacks due to various degree of damages inflicted on the ceramic during grinding operations. Due to the significance of lubrication methods in the outcome of the grinding operations, there has recently been increase need for alternative lubrication techniques for grinding of the advanced engineering ceramics. Several findings from previous works indicated that the nanofluid MQL technique is a viable option of lubrication in the grinding process. Studies have shown that the Minimum Quantity Lubrication (MQL) method has better tribological ability than the flood cooling lubrication system during grinding of advanced engineering ceramics. Furthermore, the MQL technique (a highly efficient and eco-friendly lubrication method), is being used to reduce the different types of surface and subsurface damages, while significantly reducing the consumption of lubricants. This work involves optimization and experimental study on the performance of the Silicon dioxide-based MQL nanofluids in both conventional and ultrasonic assisted grinding of Si3N4 ceramic. The MQL nano-lubricant utilized was prepared by suspending silicon dioxide (SiO2) nanoparticles in biodegradable vegetable oils. The MQL nanofluids were used to conduct grinding operations on the Si3N4 ceramic, using different process parameter settings. The results of the tangential and normal grinding forces, surface quality was analyzed using Taguchi and ANFIS modelling technique. Moreover, the effect of the grinding parameters i.e. feed rate, depth of cut, type of diamond wheel and lubrication type, were investigated on the output parameters (grinding forces, workpiece surface roughness, surface damages and wheel wear). Furthermore, the adaptive neuro fuzzy inference system (ANFIS) prediction method was used to predict and analyze the variation of the input parameters with the performance parameters. The developed ANFIS prediction model was found suitable for predicting the performance of the grinding operations. The findings in this work indicate that by increasing the nanofluid concentration, there is resultant decrease of the grinding forces, with subsequent improvement of the surface quality. In addition, it was found that that the introduction of the ultrasonic vibrations onto the workpiece material during grinding operations helps to reduce grinding forces and surface roughness significantly. The self-sharpening phenomenon found in the ultrasonic assisted grinding (UAG) process was found responsible for the improved machining performance of the UAG process. Hence, hybridizing the UAG process with biodegradable oil based nanofluids in the MQL technique was found to improve the machining performances of the grinding process, achieving better performance as the non-biodegradable lubricants. As such, the combined setup of the MQL nanofluid system with the Ultrasonic grinding system is vital for improved performance during machining of Si3N4 ceramic.